Plasma 25-Hydroxyvitamin D Levels and Survival in Patients with Advanced or Metastatic Colorectal Cancer: Findings from CALGB/SWOG 80405 (Alliance) - Yuan, Chen (Clin Cancer Res, 2019)
PURPOSE: Previous studies have suggested that higher circulating 25-hydroxyvitamin D [25(OH)D] levels are associated with decreased colorectal cancer (CRC) risk and improved survival. However, the influence of vitamin D status on disease progression and patient survival remains largely unknown for patients with advanced or metastatic CRC. EXPERIMENTAL DESIGN: We prospectively collected blood samples in 1,041 patients with previously untreated advanced or metastatic CRC participating in a randomized phase III clinical trial of first-line chemotherapy plus biologic therapy. We examined the association of baseline plasma 25(OH)D levels with overall survival (OS) and progression-free survival (PFS). Cox proportional hazards models were used to calculate hazard ratios (HRs) and confidence intervals (CIs), adjusted for prognostic factors and confounders. RESULTS: At study entry, 63% of patients were vitamin D deficient (<20 ng/mL) and 31% were vitamin D insufficient (20 to <30 ng/mL). Higher 25(OH)D levels were associated with an improvement in OS and PFS (P(trend)=0.0009 and 0.03, respectively). Compared to patients in the bottom quintile of 25(OH)D (≤10.8 ng/mL), those in the top quintile (≥24.1 ng/mL) had a multivariable-adjusted HR of 0.66 (95% CI, 0.53 to 0.83) for OS and 0.81 (95% CI, 0.66 to 1.00) for PFS. The improved survival associated with higher 25(OH)D levels was consistent across patient subgroups of prognostic patient and tumor characteristics. CONCLUSIONS: In this large cohort of patients with advanced or metastatic CRC, higher plasma 25(OH)D levels were associated with improved OS and PFS. Clinical trials assessing the benefit of vitamin D supplementation in CRC patients are warranted.